Accuracy of polarized non-contact dermoscopy and skin scraping in suspected scabies infestation. - Zulkarnain, I.; Kurniati, D.; Listiawan, M.Y.; Prakoeswa, C.R.S. (European Journal of Pediatric Dermatology, 2018)
The diagnosis of scabies infestation by clinician is commonly based on clinical patognomonic scabies signs and symptoms. However, misdiagnosis frequently occurs because some scabies manifestations mimic other diseases particularly in children leading to inaccurate treatment. Hence, it is necessary to establish definitive diagnosis by finding the Sarcoptes scabiei mite or eggs and scibala that are traditionally done by skin scraping. Unfortunately, this method is unpractical, traumatic, skill oriented, and difficult to apply in children. For this reason, we need another practical, easy, non-invasive, and accurate method. This study gives evidence that dermoscopy offers the solution. This is an analytic observational cross sectional study on 44 children in a Pesantren (School of Qoranic Study). The sensitivity of dermoscopy were 94% with specificity 69.2%, the positive predictive value was 68% and negative predictive value 94.7%, the positive likehood ratio was 3.05, and accuracy 79.5% with significant association p< 0.001. Dermoscopy is a potential diagnostic tool for screening of scabies infestation.